Cite this economics paper! It is time for the house of cards to fall down - Steven Payson (Open Economics, 2019)
This paper takes a fresh look at citation counts and publications in top-rank journals, which the academic economics profession uses to evaluate and promote its members. It first examines how and why citations are mentioned in an article, and what this implies about their counts. The discussion then examines how average citation counts to articles are used to rank journals, and the paper reviews the concerns that have been expressed about this practice. These concerns identify the large variance in citation counts among articles of the same journal, implying that those articles themselves must vary greatly in quality (Engemann and Wall 2009). To address these concerns, the paper proposes the classification of citations into three categories: Fodder Citations (for references that contribute only trivially to a paper), Relevant Citations (which substantively contribute to the paper, though the paper would remain roughly the same without them), and Essential Citations (which have a major influence). The paper argues that counts of citations by the last two categories offers greater credibility in the application of citation counts to evaluate economic literature. Finally, the paper provides an opportunity for economists to participate in a new project that solicits information on citations by these categories.
Keywords: 330; citations; economists; journals; publications; ranks